1, 3‐Dioleoyl‐2‐palmitoylglycerol‐rich human milk fat substitutes: Production, purification, characterization and modeling of the formulation. Issue 3 (13th December 2013) - Qin, Xiao‐Li; Zhong, Jin‐Feng; Wang, Yong Hua; Yang, Bo; Lan, Dong‐Ming; Wang, Fang‐Hua
<x xml:space="preserve">Abstract</x> Human milk fat substitutes (HMFS) were prepared by enzymatic synthesis combined with physical blending methods. As the main constituents in HMFS, 1, 3‐dioleoyl‐2‐palmitoylglycerol‐rich TAGs (OPO‐rich TAGs) were synthesized in one step by Lipozyme RM IM‐catalyzed acidolysis of 34L‐leaf lard and then purified by molecular distillation. The results showed that OPO‐rich TAGs with purity of 91.39wt% were obtained at evaporation temperature of 180°C and a pressure of 6.7–7.5 Pa. Furthermore, a mathematical model was established for formulating HMFS by blending OPO‐rich TAGs product with the selected vegetable oils. Under the blending ratio of 0.6700:0.1638:0.1627:0.0035:0.0000 (OPO‐rich TAGs product/coconut oil/soybean oil/flaxseed oil/sunflower seed oil), the HMFS had fatty acids levels similar to those of human milk fat (HMF), and kept a high proportion (about 70%) of C16:0 at the sn‐2 position. Based on the fatty acid composition and distribution of HMF and "deducting score" principle, the similarity of HMFS to HMF was assessed by the related model, and the score for the similarity of HMFS to HMF was 85.54 points, indicating that this HMFS can be used as a fat substitute in infant formula. This study can provide valuable information on preparing HMFS and will be helpful for the infant formula industry. Practical applications: The information on the whole process of the production of HMFS, including one‐step enzymatic synthesis, purification, quality evaluation and physical blending, is important for the development of infant formula with high quality. The enzymatic synthesis combined with physical blending methods enable a high similarity of HMFS to human milk fat and the HMFS can be used a potential fat substitute in infant formula.